Analisis Kesalahan Ortografi Bahasa Arab Mahasiswa Pendidikan Bahasa Arab Universitas Muhammadiyah Malang - Thoyyibah, Anisatu (Institut Agama Islam Negeri (IAIN) Curup, 2019)
This article is a study of Arabic Language Education students at the University of Muhammad Malang concerning spelling errors in writing Arabic characters. Orthography or Arabic alphabet spelling is a system that is generally used to realize the sound description from spoken language to written language in a language community, in this case Arabic. But in practice not everyone is able to describe the sound of language into writing correctly. Including students in the Arabic Language Study Program, University of Muhammadiyah Malang. This research is a descriptive type, in collecting data using observation techniques, documentation techniques, and interview techniques. The data analysis uses the orthographic equivalent method with basic techniques (orthographic sorting techniques) and advanced techniques (comparative correlation techniques). While the presentation of data uses informal variety. The results showed that the forms of orthographic errors or Arabic characters were first, one type of error consisting of adding vowels, reducing vowels or consonants, reducing consonant punctuation, and changing letters. Second, two or more types of errors. The factors underlying these mistakes are in terms of sociolinguistics and psycholinguistics.